2014
DOI: 10.1111/mmi.12859
|View full text |Cite
|
Sign up to set email alerts
|

Molecular details of a starch utilization pathway in the human gut symbiont Eubacterium rectale

Abstract: Summary Eubacterium rectale is a prominent human gut symbiont yet little is known about the molecular strategies this bacterium has developed to acquire nutrients within the competitive gut ecosystem. Starch is one of the most abundant glycans in the human diet, and E. rectale increases in vivo when the host consumes a diet rich in resistant starch, although it is not a primary degrader of this glycan. Here we present the results of a quantitative proteomics study in which we identify two glycoside hydrolase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 88 publications
3
97
0
Order By: Relevance
“…We previously reported that E. rectale Amy13K (EUR_21100) was likely comprised of five CBMs at its N‐terminus based on weak sequence homology to the starch‐binding families CBM26 (BLAST E ‐value 2e −5 ) and CBM41 (BLAST E ‐value 1e −5 – 5e −7 ) (Cockburn et al , ). The biochemical and structural data presented here supports that there are five CBMs, labeled as CBMa‐e and two warrant classification into new CBM families (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that E. rectale Amy13K (EUR_21100) was likely comprised of five CBMs at its N‐terminus based on weak sequence homology to the starch‐binding families CBM26 (BLAST E ‐value 2e −5 ) and CBM41 (BLAST E ‐value 1e −5 – 5e −7 ) (Cockburn et al , ). The biochemical and structural data presented here supports that there are five CBMs, labeled as CBMa‐e and two warrant classification into new CBM families (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For activity assays with polysaccharide substrates the production of free reducing ends was monitored using the bicinchoninic acid (BCA) method (Waffenschmidt and Jaenicke, ) as previously described (Cockburn et al , ). All reactions included 10 mM HEPES pH 6.5, with 5 mM CaCl 2 and 0.02% Tween80.…”
Section: Methodsmentioning
confidence: 99%
“…Ruminococcus bromii has been identified as the primary degrader of resistant starch in the human gut (23), although Bifidobacterium adolescentis strains were also reported to possess growth capabilities on this substrate (15). Major commensals from the Bacteroides genus (47) and the butyrate-producing Firmicutes member Eubacterium rectale (14) are other HGM members with considerable starch growth and degradation capabilities. Common to these bacteria is that they possess highly modular extracellular cell-attached enzymes with one or more catalytic modules and multiple carbohydrate binding modules (CBMs), which mediate tight binding to starch substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the diversity of enzymes complements employed, the strategies used to capture hydrolyzed starch in the gut are a function of the unique physiology of the respective microorganisms [1417]. The Gram-positive Firmicutes and Actinobacteria take up monosaccharides and oligosaccharides via a variety of transport systems including ATP-binding cassette transporters, major facilitator superfamily, and phosphotransferase systems [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-positive Firmicutes and Actinobacteria take up monosaccharides and oligosaccharides via a variety of transport systems including ATP-binding cassette transporters, major facilitator superfamily, and phosphotransferase systems [18, 19]. Many of these transporters are encoded within putative operons that include one or more extracellular GH13 enzymes to hydrolyze starch at the cell surface [14, 17, 20]. In contrast, the genomes of most Bacteroidetes, the dominant Gram-negative phylum in the mammalian gut, have far fewer of these classically studied carbohydrateuptake systems [21].…”
Section: Introductionmentioning
confidence: 99%